PERBANDINGAN MODEL REGRESI NONPARAMETRIK SPLINE DAN REGRESI NONPARAMETRIK KERNEL - , YUNI KURNIA P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Regression analysis is a statistical tool that is widely used to determine the relationship between a pair of variables or more. Regression analysis is divided into two, namely parametric regression and nonparametric regression. Nonparametric regression has several smoothing methods, such as spline and kernel regression. Its main purpose is to compare the two methods for estimating the nonparametric regression model. The data were used to compare the two methods of toddler growth data.